Gadget Addiction and Time Management of The University Student - Febria Nurmelia Marlina; Irwan Cahyadi; Layali Ihyani; Ega Dwi Putri Marswandi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
This study aims to analyze the effect of gadget addiction on organizational time management of students in the Management Study Program at Bumigora University. The method used in this study is a quantitative approach . Data were collected using a questionnaire that measures two main variables: gadget addiction (X) and time management (Y). A simple linear regression test was conducted to examine the effect of gadget addiction on time management. The results showed that gadget addiction has an effect on time management, with a regression coefficient value of 0.4723. Simultaneous testing also confirmed that gadget addiction has a significant influence on students' overall time management. In addition, the coefficient of determination (R²) of 0.5462 indicates that approximately 54.62 % of the variation in time management can be explained by gadget addiction. This study provides important insights for student organizations and educational institutions to improve time management by controlling excessive gadget use, in order to increase organizational productivity and performance.